The impact of strategic transport policies on future urban traffic management systems. (September 2021) - Grote, Matt; Waterson, Ben; Rudolph, Felix
Abstract: Urban traffic management and traffic signal control systems, denoted as Urban Traffic Control (UTC) systems, are used extensively worldwide by Local Government Authorities (LGAs) when implementing strategic transport policies. However, it is not clear how well the requirements imposed by LGA policy implementation will be met by UTC systems being developed for the future. Therefore, research was undertaken to analyse how delivery of urban transport policies over the next 5–10 years would shape LGAs' requirements for the next generation of UTC systems, and thereby to identify Key Performance Indicators (KPIs) to provide user-led guidance for future system development. A two-stage survey of LGA policy makers and implementers from around the world was conducted. The results produced consensus among the group of participants (n = 16) on 17 KPIs, representing a synthesis of expert opinions on the desired features of future UTC systems from a policy implementation perspective. The research makes an important contribution in eliciting the wide-ranging breadth of issues associated with delivering strategic transport policies and understanding how these issues affect the requirements LGAs have for future UTC systems. Aligning future UTC system capabilities with LGAs' requirements will enable more effective implementation of strategic urban transport policies worldwide and allow the benefits to society associated with those policies to be realised. Highlights: Local Government Authorities (LGAs) implement strategic transport policies. Policy implementation is achieved using urban traffic management systems. LGA policy makers and implementers were interviewed about desired system features. Consensus was achieved on Key Performance Indicators (KPIs) for future systems. The KPIs provide user-led guidance to align system capabilities with LGA policies.